Temperature-controlled Se-S isotope fractionation during seawater mixing and sulfide precipitation in black smoker chimneys - Grosche, Anna; Keith, Manuel; Klemd, Reiner; Strauss, Harald; Rosca, Carolina; König, Stephan (Geochimica Et Cosmochimica Acta, 2024)
Submarine hydrothermal venting leads to the formation of black smoker chimneys with complex internal zoning. These emerge through mineral precipitation under changing fluid conditions caused by variable degrees of fluid-seawater mixing. This study explores the potential of selenium (Se) isotopes as a novel tool to understand the enrichment processes and identify the sources of chalcophile elements in seafloor hydrothermal systems. In-situ trace element analysis of hydrothermal sulfides combined with high-precision Se and S isotope analysis of micro-domains through the wall of black smoker chimneys from the Nifonea vent field (New Hebrides back-arc, SW Pacific) revealed variations in sulfide chemistry at small spatial resolution. The δ82/76Se values (deviation of 82Se/76Se relative to NIST SRM 3149) of the sulfide micro-domains range from +0.6 to −3.7 ‰ ± 0.2 ‰ (2 s.d.) with a general decrease from the inner chalcopyrite lining towards the outer chimney wall. The highest δ82/76Se values overlap with the mean value of fresh basaltic glass from Nifonea caldera (+0.6 ± 0.4 ‰, n = 4), indicating that Se is primarily leached from the surrounding back-arc basalts. The trace element contents of sulfides revealed systematic variations between vent sites, linked to differences in fluid vapor content induced by sub-seafloor boiling, which did not cause any Se isotope fractionation. Instead, decreasing Se/Tl ratios of pyrite together with decreasing δ82/76Se values of sulfide micro-domains and calculated δ34SH2S fluid values towards the outer chimney wall are indicative of temperature-dependent Se and S isotope fractionation at 370 to <200 °C during fluid-seawater mixing within the chimney wall. This study presents Se isotopes as a new robust instrument to unravel the sources of chalcophile elements and related fluid processes in seawater-diluted hydrothermal systems, enhancing our understanding of their geochemical complexities.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Black smoker; Hydrothermal vent; Metal sources; Selenium; Stable isotopes